Penerapan Konseling Kelompok SFBC Bermuatan Nilai-Nilai Al-Qur’an Untuk Meningkatkan Self-Efficacy Santri Hafidzah di PPHQ Putri 4 Al-Karima Pare - Arifah Fitria Hidayati; Nur Mega Aris Saputra (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
This study was conducted to test the application of Solution Focused Brief Counseling (SFBC) containing the values ​​of the Qur'an in counseling groups to improve the self-ability of hafidzah students at the Hamalatul Qur'an Putri 4 Pare Islamic Boarding School. This study used a quasi-experimental research type with a one-group pre-test and post-test design. The subjects in this study were 6 students out of 23 hafidzah students who had low self-efficacy. The data collection method used was a questionnaire with a self-efficacy scale. The type of questionnaire used was a closed questionnaire with a Likert scale to measure attitudes containing 4 alternative answers, namely strongly agree, agree, disagree, and strongly disagree. In this case, the researcher conducted data analysis with one of the most common procedures in non-parametric, namely The Wilcoxon Signed-rank Test using the SPSS (Statistical Product and Service Solution) version 21.0 assistance program. The Wilcoxon test results show Z = -2.201 with p = 0.036 (<0.05). Since the p value is smaller than 0.05, there is a statistically significant difference between the pre-test and post-test scores. Thus, H₀ is rejected and Hi is accepted, so Ho is rejected, which means that SFBC Group Counseling Containing Al-Quranic Values ​​has an effect on increasing the self-efficacy of hafidzah students.